2011
DOI: 10.1007/s11214-011-9850-4
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Magnetospheric Equatorial Regions at Saturn from Cassini Prime Mission Observations

Abstract: Saturn's rich magnetospheric environment is unique in the solar system, with a large number of active magnetospheric processes and phenomena. Observations of this environment from the Cassini spacecraft has enabled the study of a magnetospheric system which strongly interacts with other components of the saturnian system: the planet, its rings, C.S. Arridge ( ) ·

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 238 publications
(265 reference statements)
2
35
0
Order By: Relevance
“…Arridge et al 2011c) about Titan's location can also produce strong changes in the charged particle environment in which Titan is embedded, and strong rotations in the convection electric field. The motion of the plasma sheet implies strong changes in the plasma density and hence ram and plasma pressure.…”
Section: Key Processes In the Formation Of Titan's Induced Magnetospherementioning
confidence: 99%
See 1 more Smart Citation
“…Arridge et al 2011c) about Titan's location can also produce strong changes in the charged particle environment in which Titan is embedded, and strong rotations in the convection electric field. The motion of the plasma sheet implies strong changes in the plasma density and hence ram and plasma pressure.…”
Section: Key Processes In the Formation Of Titan's Induced Magnetospherementioning
confidence: 99%
“…In this section we introduce the structure and physics of Saturn's magnetosphere particularly focusing on the region near Titan's orbit at 20.3 R S . For detailed recent reviews of the Saturnian magnetosphere and its configuration we refer the reader to , Gombosi et al (2009) and Arridge et al (2011c). The basic configuration and physics of Saturn's magnetosphere is presented in Sect.…”
Section: Structure and Physics Of Saturn's Magnetosphere Near Titanmentioning
confidence: 99%
“…The former is obtained by integrating the exobase CH 4 EDF over the full momentum space occupied by realistic particle trajectories that cross the exobase with upward velocities, and the latter obtained by integrating the same EDF over a restricted momentum space with kinetic energy greater than the local escape energy. The Chamberlain model used in Section 4 implicitly assumes an ideal Maxwellian for the exobase CH 4 EDF, given by Arridge et al 2011b). Clearly, existing studies predict a wide range of CH 4 escape rates from negligible to several 10 27 s −1 , with the lower limit being compatible with the Chamberlain model presented in Section 4.…”
Section: Implications For Ch 4 Escape From Titanmentioning
confidence: 86%
“…At Saturn it has been found that the magnetodisk is bowl-shaped due to the tilt angle of the equatorial plane relative to the ecliptic plane and is a seasonal effect. The magnetodisk and the associated current sheet are also flapping up and down as discussed by Arridge et al (2011) and Volwerk et al (2013). The main transport processes in the magnetosphere like interchange motion and injection events are, very similar to the Jupiter case, continuously present in the Kronian magnetosphere showing the highly dynamic nature of Saturn's magnetosphere Paranicas et al 2010).…”
Section: Middle Magnetosphere and Magnetodiskmentioning
confidence: 90%
“…Characteristic key regions of giant planet magnetospheres are usually subdivided into inner, middle and outer magnetosphere (Bagenal 1992;Arridge et al 2011), whereas the distance of transition between them is widely fluctuating. In both magnetospheres we find strong dipolar intrinsic magnetic fields in the innermost magnetospheres, the region of the radiation belts populated with the high-energy electrons and ions with different origins.…”
Section: Introductionmentioning
confidence: 99%